Linking The Learning of Malal Creeds To P5/PPRA: Building a Strong Moral and Citizenship Foundatio - Abdul Fatah; Murdianto; Abdur rahman (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to examine the integration of Akidah Ahlak learning with the Pancasila and Rahmatan lil Alamin Student Profile Strengthening Project (P5/PPRa) in building moral and national character in madrasahs. With a qualitative descriptive approach, this study examines the process of internalizing the values of faith, piety, and noble morals that are in line with moderate, tolerant, and inclusive characters as emphasized in P5/PPRa. The results of the study indicate that although the implementation of the program still encounters obstacles, such as minimal teacher understanding and limited facilities, this integration has begun to show a positive impact on the formation of student character. Contextual project activities are able to encourage student involvement in social and religious activities. From these findings, it is recommended that collaboration between teachers, students, and stakeholders is important in developing a curriculum that combines religious and national values to strengthen student identity in the global era